PENGARUH JUMLAH BAKTERI METHANOBACTERIUM DAN LAMA FERMENTASI TERHADAP PROPORSI GAS METANA (CH4) PADA PENGOLAHAN SAMPAH ORGANIK DI TPA SUWUNG DENPASAR - Yudiandika, I. Putu; Suarna, I Wayan; Sudarma, I Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2017)
EFFECT OF NUMBER OF METHANOBACTERIUM AND FERMENTATION DURATION TO METHANE (CH4) GAS PROPORTION IN ORGANIC WASTE PROCESSING IN SUWUNG TPA DENPASAR A research has been conducted to find out the effect to the amount of methanobacterium bacteria and fermentation duration toward proportion of methana (CH 4 ) at organic waste processing at TPA Suwung Denpasar. Methana gas produced from this organic waste will be processed become fuel of electric generation. From this study will be expected to get all methana gas that contained at the waste so that there is no methana gas loss to the atmosphere. This study was conducted by using 4 treatments that are without bacteria (B0), bacteria with number of population  10 6   CFU/ml (B1), bacteria with population of 10 7 CFU/ml (B2), and bacteria with population of 10 8 CFU/ml (B3). Each treatment conducted thrice (3) repeat. The four treatments conducted measurement of gas variable after fermentation during 0 week, 3 weeks, 5 weeks, 7 weeks and 9 weeks by uisng gas analyzer  GA 2000 Geotech. Data from study result then analyzed by using complicated factorial design (RAL). From ANOVA analysis shows there was significant bacteria number and fermentation duration toward proportion or procentage of methana gas resulted. The longer fermentation time takes place, the bigger the proportion of the methane gas produced.  However, the greater number of the bacteria population does not always produce bigger proportion of methane gas To find out the combination which could give best effect the researcher used Duncan test. The result of analysis from Duncan shows that combination at the ninth weeks by number of bacteria 10 7 CFU/ml giving best result that was percentage of methana gas is 55,10%.